2019
DOI: 10.1002/acn3.50936
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐life and late‐life vascular risk factor burden and neuropathology in old age

Abstract: ObjectiveTo determine whether vascular risk factor burden in mid‐ or late‐life associates with postmortem vascular and neurodegenerative pathologies in a community‐based sample.MethodsWe studied participants from the Framingham Heart Study who participated in our voluntary brain bank program. Overall vascular risk factor burden was calculated using the Framingham Stroke Risk Profile (FSRP). Mid‐life FSRP was measured at 50 to 60 years of age. Following death, brains were autopsied and semi‐quantitatively asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…However, the association of diabetes or hypertension with AD pathology was not found in other studies 18–20 . Moreover, mid‐life vascular risk burden assessed by the Framingham Stroke Risk Profile was predictive of cerebrovascular pathologies, but not AD pathology 22 . In addition, another autopsy study showed the association between dementia risk score (incorporating age, sex, education, SBP, BMI, cholesterol, physical activity, and APOE ε4 status) and cerebral infarcts 32 .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, the association of diabetes or hypertension with AD pathology was not found in other studies 18–20 . Moreover, mid‐life vascular risk burden assessed by the Framingham Stroke Risk Profile was predictive of cerebrovascular pathologies, but not AD pathology 22 . In addition, another autopsy study showed the association between dementia risk score (incorporating age, sex, education, SBP, BMI, cholesterol, physical activity, and APOE ε4 status) and cerebral infarcts 32 .…”
Section: Discussionmentioning
confidence: 90%
“…Few studies have shown the association of diabetes or hypertension with AD pathology such as neuritic plaques and neurofibrillary tangles 17,21 . However, other studies have shown that diabetes, hypertension, or the Framingham Stroke Risk Profile (including age, systolic blood pressure, current smoking status, antihypertensive medication use, prevalent diabetes, prevalent CVD, and prevalent atrial fibrillation) is related to cerebrovascular pathologies (including cortical infarctions and arteriosclerosis stage) but not AD pathology 18–20,22 . Possible explanations for the discrepancies could be explained by the differences in age of the study populations, study settings, ascertainment of the exposure, assessment of brain pathologies, follow‐up time, and major causes of death among these studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Vascular risk factors have been associated with amyloid and tau deposition, by positron emission tomography, or other Alzheimer disease (AD) biomarkers, in some 14 but not all studies. 15,16 Because overlapping pathologies are common in dementia, vascular mechanisms are often relevant. In the Religious Order Study/Rush Memory and Aging Project, individuals clinically diagnosed with mild cognitive impairment (MCI) or AD frequently had infarcts and mixed pathology on postmortem evaluation.…”
Section: Vascular Brain Healthmentioning
confidence: 99%
“…Brain donation is part of the ROS and MAP study protocols and each participant signed an Anatomic Gift Act in addition to informed consent and a repository consent allowing their biospecimens and data to be repurposed. Details of study design for each of these cohorts has been previously published [28][29][30]. Dissection of frozen hypothalamus and nucleus accumbens was done by a single pathologist at each site.…”
Section: Sample Informationmentioning
confidence: 99%